STOCHASTIC CONTROL INFORMATION SYSTEMS THE AVIATION GAS TURBINE ENGINE - Tovkach, Serhii (Proceedings of National Aviation University (archive), 2019)
Development of a robust system for the detection of self-tuning parameter regulator in automatic control system gas turbine engines (ACS GTE) will benefit both military and civil aviation through improved aircraft reliability and maintainability. Presented is a gas turbine engine stochastic information system that integrates information from various advanced control analysis techniques to achieve robust self-tuning loop awareness. This paper presents the computational techniques for identifying the accurate sequence parameter regulator by using: firstly, the Lyapunov function application with the performance analyzer for ensuring the stability of optimization processes; secondly, the Wiener-Hoph function application with the white noise generator (random processes) for defining the intensity and impulse transition function of the signal, as a result, accurate set up of the aviation engine control unit. The main control loop is represented by a transfer function of the object and the regulator, their self-tuning models, criteria for setting regulator parameters and sensitive function. An important feature of the information system GTE is the presence of heterogenous hardware and software, which is often associated with a long period of taking system into operation, it is necessary to use the portable serving device and request host for satisfying the requirements of the correct engine operation.